“Dari Tambang ke Tenun: Transformasi Sosial-Ekonomi Mantan Pekerja Tambang di Silungkang Pasca Penutupan Tambang Ombilin (2016–2024)” - Windy Anggreani Saputri; Etmi Hardi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the social and economic transformation experienced by former coal mine workers in Silungkang District, Sawahlunto City, following the closure of the Ombilin Coal Mine in 2016. The termination of mining operations marked a turning point for a community that had long depended on the extractive industry. The sudden loss of employment forced many former miners to adapt and seek new sources of livelihood. One significant adaptation was the shift from industrial labor to traditional craftsmanship, particularly to the production of songket weaving a cultural heritage deeply rooted in Silungkang society.This research employs a qualitative approach with a social-historical method. Data were collected through in-depth interviews, direct observation, and analysis of relevant archives and documents. These methods were used to understand the personal experiences of former miners in the process of occupational transition, as well as to examine how this transformation reshaped their social identity and community dynamics.The findings reveal that the transition from mining to weaving represents more than an economic survival strategy; it reflects a profound redefinition of social identity. Former miners who once worked in the industrial sector have rebuilt their lives through weaving and small-scale entrepreneurship. The involvement of family members, community solidarity, and government training programs have further supported the sustainability of this new livelihood.This phenomenon demonstrates the remarkable adaptability of the Silungkang community in responding to structural change. Through the revival of songket weaving, former miners have not only created new economic opportunities but also preserved and revitalized their cultural identity in the post-mining era.